ANALISIS PEMBENTUKAN KARAKTER SISWA SEKOLAH DASAR MELALUI CERITA LEGENDA MALIN KUNDANG - Rina Marlina; Yeni Erita (STKIP Subang, 2022)
This study intends to analyze the character formation of elementary school students through the legendary story of Malin Kundang. The research method used is library research. The research data collection tool used is from the library, reading and analyzing sources, and compiling writing. The results of this study indicate that the mythology of Malin Kundang has a number of educational characters. One of them is the value of morality in Malin Kundang; morality human relationship with himself.It can be concluded that the legend of Malin Kundang can be used as a medium for building the character of elementary school children